Engineering for the future proceedings of a conference organized by the Association of Municipal Engineers and held at the University of Stirling on 11-15 June 1984. (Thomas Telford, 1984)
Providing access to engineering content from the past, this is the proceedings of the Association of Municipal Engineers' annual conference held in 1984.